Oral immunoprophylaxis of finfish using alginate microencapsulation - Bikramjit Ghosh; Cain, KD; Barbara Nowak; Andrew Bridle (2014)
Oral delivery is a potential solution to constraints associated with the immunoprophylaxis methods most prevalent in aquaculture: injection and immersion. However, oral immunogen delivery has produced inconsistent outcomes in fish. This is primarily attributed to antigen degradation, solutions to which are typically complex and expensive. Here, we developed and validated a method for oral fish immunoprophylaxis using alginate microcapsules (aMCs). An emulsion/internal-gelation protocol was adapted to minimize impact on the material being encapsulated. Microcapsules were characterized in vitro using lysozyme and bovine serum albumin (BSA). Post-encapsulation change in bioactivity of lysozyme was used to determine protocol impacts on the encapsulated substance. aMC release dynamics were tested at different pH levels and temperatures using BSA. Uptake and systemic distribution was verified using FITC-labeled BSA-aMCs ex vivo in intestinal explants, and combined in feed for in vivo administration to Salmo salar fry. Oncorhynchus mykiss fry were immunized against Flavobacterium psychrophilum infection with microencapsulated live attenuated oral vaccine. Microencapsulation did not significantly reduce lysozyme bioactivity. BSA release from aMCs was pH- and temperature-responsive. Uptake and translocation of aMCs was visible ex vivo and in vivo . Oral immunization significantly increased survival against bacterial challenge (F=11.4; p=0.01), and was comparable to IP immunization. Our findings indicate this method could be a convenient, effective alternative to prevalent finfish immunoprophylaxis strategies.